The Analysis and Optimization of Anji Rammed Earth House's Envelope Thermal Characteristic. (6th January 2016) - Xinxin, Lin; Meiyan, Wang; Fukuda, Hiroatsu
Abstract: To explore the applicability of rammed earth in China's rural buildings, we took the Anji RE house for study. This paper performed an analysis on materials and envelope thermal characteristic, results showed that the average heat transfer coefficient of the RE wall is 1.52W/(m 2 ·k) which meets the related thermal codes. After roof modification using the lightweight clay measuring which the conductivity coefficient is 0.1216 (W·m -1 ·K -1 ), the average heat coefficient of two roofs (air-insulation roof and lightweight clay roof) are respectively 0.654W/(m 2 ·k), 0.268W/(m 2 ·k) that also meet the related codes.